A method for preparing rock material containing internal crack defects and its application
By preparing nano-carbon silicon modified rosin and rock-like materials, laminar casting and evaporating at high temperature, the problem of difficult to truly simulate the internal crack defects of rock materials in the prior art is solved, and the high reality of rock-like materials is achieved Improvement of sexuality and scope of application.
Patent Information
- Application Number
- CN202411614453.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-13
AI Technical Summary
The prior art is difficult to truly simulate internal crack defects in rock materials, resulting in significant differences in experimental results and actual phenomena. The performance of rock-like materials is insufficient and it is difficult to control internal crack defects.
By preparing nano-carbon silicon modified rosin and mixing it with a mixed slurry of rock-like materials, it is formed under constant temperature and humidity conditions by laminar casting. Finally, the nano-carbon silicon modified rosin is evaporated at high temperature to form an internal content. Fracture defective rock-like materials.
The real simulation of internal cracks of rock-like materials is achieved, and the generation of internal cracks is relatively easy, which enhances the authenticity and scope of application of rock-like materials, while reducing the release of harmful substances and making the process environmentally friendly.
Smart Images

Figure CN119124787B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rock mass engineering, and in particular to a method for preparing rock materials containing internal crack defects and application thereof. Background Art
[0002] There are various defects in natural rock mass, which pose a serious threat to the safe construction of rock mass engineering. To this end, domestic and foreign scholars have conducted a lot of research on rock mass with defects. During the research, scholars found that natural rock mass has high discreteness, which biases the accuracy of the test results. Therefore, in order to reduce the test error caused by the high discreteness of natural rock mass, some scholars chose artificially prepared rock-like materials to study the crack propagation law and failure instability mechanism of defective rock mass, and verified the accuracy of the method through corresponding theoretical analysis and simulation inversion.
[0003] In the existing research on the failure law and mechanism of defective rocks, scholars have carried out research on prefabricated through cracks, surface non-through cracks, holes, through crack groups, surface non-through crack groups, etc., and achieved good results. In addition to the above types of cracks, there are also internal cracks in the rock mass. However, due to the opacity of the rock mass, the location of the internal rock mass cracks is difficult to determine, which brings huge safety hazards to the construction of rock mass engineering.
[0004] Some scholars have tried to study transparent materials instead of rock materials, and to replace internal cracks with embedded weak media with obvious mechanical properties different from those of transparent materials to study the internal crack expansion law and failure instability mechanism. However, due to the obvious difference in mechanical properties between transparent materials and rock materials, the internal weak medium is very different from the actual crack properties, which leads to obvious differences between the experimental results and the actual phenomena.
[0005] At the same time, some scholars choose to create internal cracks in rock-like materials through paraffin. Use high temperature to melt the paraffin into liquid, thereby forming internal cracks. However, when the temperature returns to normal temperature, the paraffin solidifies again and fills the cracks. Although rock-like materials have similar properties to rock masses, the presence of paraffin in internal cracks affects the accuracy of the test results. In addition, some scholars choose to create internal cracks in rock-like materials through volatile substances, and use their volatility characteristics to form internal cracks. However, after the volatile substances evaporate, it is easy to cause the crack resistance and durability of rock-like materials to decrease, and it is impossible to truly restore the rock materials, and thus cannot meet the research needs of internal cracks in rock masses. Summary of the invention
[0006] In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing rock-like materials containing internal cracks and defects, which can truly simulate rock materials and solve the problems of insufficient performance of rock-like materials and difficulty in controlling internal cracks and defects in the prior art.
[0007] To achieve the above object, the present invention provides the following solutions:
[0008] A method for preparing a rock material containing internal crack defects comprises the following steps:
[0009] Preparation of nano-carbon silicon material modified rosin;
[0010] Select appropriate materials to prepare mixed slurry of rock-like materials and meet the particle grading requirements;
[0011] The nano-carbon silicon modified rosin is mixed with the mixed slurry, and stirred evenly to obtain a mixture;
[0012] Select and assemble a casting mold according to test requirements, slowly and evenly inject the mixture into the casting mold by laminar casting, vibrate and shape it, and maintain it under constant temperature and humidity conditions;
[0013] After forming, the casting mold is removed, and the formed sample is placed in a heating furnace for high-temperature curing to obtain a rock-like material containing internal crack defects.
[0014] Preferably, the process for preparing the nano-carbon silicon material modified rosin is as follows: first, rosin and nano-carbon silicon material are added to a stainless steel reactor, and then a volatile organic solvent is added to the stainless steel reactor, and stirred evenly using a high-speed stirrer; then the stainless steel reactor is heated to a reflux state, the temperature is controlled between 60 and 80° C., and maintained for 1 to 2 hours; then, while maintaining the temperature, a cross-linking agent and an initiator are added dropwise, the stirring continues to be evenly uniform, and the temperature of the stainless steel reactor is increased to between 80 and 100° C., and the reaction is carried out for 2 to 3 hours to promote the cross-linking reaction; after the reaction is completed, the mixed solution is cooled to room temperature, and then the remaining volatile organic solvent is removed through a decompression device to obtain the nano-carbon silicon material modified rosin.
[0015] Preferably, the volatile organic solvent is one of ethyl acetate, acetone, methanol and ethanol.
[0016] Preferably, the mixed slurry of rock-like materials is prepared by selecting corresponding materials and meeting the particle grading requirements, including: the materials of the mixed slurry are composed of crushed stone, sand, cement, clay and water, and the mass ratio of the materials is: crushed stone: sand: clay: cement: water = 3:2:1:1:0.5, and the amount of the mixed slurry is determined according to the rock material required by the test.
[0017] Preferably, the nano-carbon silicon modified rosin is mixed with a mixed slurry and stirred evenly to obtain a mixture. The specific method is: first, the mixed slurry is mixed and stirred evenly, and then the nano-carbon silicon modified rosin is put into the mixed slurry, and stirred by a stirrer until it is uniform to obtain a mixture.
[0018] Preferably, a casting mold is selected and assembled according to the test requirements, the mixture is slowly and evenly injected into the casting mold by a laminar casting method, and vibrated into shape, and then cured under constant temperature and humidity conditions. The specific method is: the mixture in a uniform state is injected into the casting mold with a layered structure, and after each layer is cast, the casting mold containing the mixture is placed on a vibration table for vibration to expel bubbles in the mixture.
[0019] Preferably, the constant temperature and humidity curing conditions are a temperature of 22-24° C. and a relative humidity of more than 90%.
[0020] Preferably, the formed sample is placed in a heating furnace for high-temperature curing to obtain a rock-like material containing internal crack defects, including: placing the formed sample in a heating furnace for curing for 24 hours, and the temperature of the heating furnace is maintained between 110 and 135°C, so that the nano-carbon silicon material modified rosin is heated and volatilized, and finally taking out the sample to obtain a rock-like material containing internal crack defects.
[0021] The present invention also provides a rock material containing internal crack defects prepared by the above method.
[0022] The present invention also provides an application of the rock material containing internal crack defects prepared by the above method in geotechnical engineering.
[0023] According to the specific embodiments provided by the present invention, compared with the prior art, the present invention discloses the following technical effects:
[0024] (1) The present invention utilizes the volatility of nano-carbon silicon material modified rosin to randomly embed the nano-carbon silicon material modified rosin into the rock-like material, thereby completing the prefabrication of internal cracks in the rock-like material and facilitating the control of the generation of internal cracks.
[0025] (2) The present invention reduces the generation of bubbles in the mixture during the casting process by the laminar casting method, ensuring the uniformity and density of the mixture. At the same time, the volatile organic solvent is used for removal and use, which reduces the release of harmful substances, has relatively little impact on the environment, and realizes the environmental protection of the process.
[0026] (3) The present invention modifies rosin by using nano-carbon silicon materials. The cracks formed after the rosin volatilizes and the nano-carbon silicon materials remaining inside can reproduce the structural characteristics inside the rock, forming a microstructure similar to that of real rocks, thereby increasing the authenticity of the rock-like materials. At the same time, it also ensures that the rock-like materials can simulate the structural characteristics of real rocks, further improving the scope of application of the rock-like materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0028] Figure 1 The present invention is a flow chart of a method for preparing rock materials containing internal crack defects. DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] In order to make the purpose, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0031] Embodiment 1
[0032] like Figure 1 As shown, the present invention provides a method for preparing a rock material containing internal crack defects, comprising the following steps:
[0033] Step 100: preparing nano-carbon silicon material modified rosin;
[0034] Step 200: Select appropriate materials to prepare a mixed slurry of rock-like materials, and meet the particle grading requirements;
[0035] Step 300: mixing the nano-carbon silicon modified rosin with the mixed slurry, and stirring evenly to obtain a mixture;
[0036] Step 400: selecting and assembling a casting mold according to test requirements, slowly and evenly injecting the mixture into the casting mold by a laminar casting method, vibrating and shaping the mixture, and curing the mixture under constant temperature and humidity conditions;
[0037] Step 500: After forming, the casting mold is removed, and the formed sample is placed in a heating furnace for high-temperature curing to obtain a rock-like material containing internal crack defects.
[0038] In the above step 100, the process of preparing the nano-carbon silicon material modified rosin is: first, add rosin and nano-carbon silicon material into a stainless steel reactor, then add a volatile organic solvent into the stainless steel reactor, and stir evenly with a high-speed stirrer; then heat the stainless steel reactor to a reflux state, control the temperature between 60 and 80°C, and maintain for 1 to 2 hours; then, while maintaining the temperature, drop a crosslinking agent and an initiator, continue to stir evenly, and increase the temperature of the stainless steel reactor to between 80 and 100°C, react for 2 to 3 hours, and promote the crosslinking reaction; after the reaction is completed, the mixed solution is cooled to room temperature, and then the remaining volatile organic solvent is removed by a decompression device to obtain the nano-carbon silicon material modified rosin. Wherein, the volatile organic solvent is one of ethyl acetate, acetone, methanol, and ethanol, preferably acetone.
[0039] In the above step 200, the corresponding materials are selected to prepare a mixed slurry of rock-like materials, and the particle grading requirements are met, including: the materials of the mixed slurry are composed of crushed stone, sand, cement, clay and water, and the mass ratio of the materials is: crushed stone: sand: clay: cement: water = 3:2:1:1:0.5, and the amount of the mixed slurry is determined according to the rock material required by the test.
[0040] In the above step 300, the nano-carbon silicon modified rosin is mixed with the mixed slurry, and the mixture is obtained after stirring evenly. The specific method is: first, the mixed slurry is mixed and stirred evenly, and then the nano-carbon silicon modified rosin is placed in the mixed slurry, and stirred to a uniform state by a stirrer to obtain a mixture. Then, according to the test requirements, the casting mold is selected and assembled, and the mixture is slowly and evenly injected into the casting mold by the laminar casting method, and vibrated to form, and maintained under constant temperature and humidity conditions. The specific method is: the mixture in a uniform state is injected into the casting mold with a layered structure. After each layer is cast, the casting mold containing the mixture is placed on a vibration table for vibration to expel bubbles in the mixture. The constant temperature and humidity curing conditions described here are a temperature of 22~24°C and a relative humidity of more than 90%.
[0041] In step 500, the formed sample is placed in a heating furnace for high-temperature curing to obtain a rock-like material containing internal crack defects, including: placing the formed sample in a heating furnace for curing for 24 hours, and the temperature of the heating furnace is maintained between 110 and 135° C., so that the nano-carbon silicon material modified rosin is heated and volatilized, and finally taking out the sample to obtain a rock-like material containing internal crack defects.
[0042] The rock-like material obtained by the method for preparing a rock-like material containing internal crack defects according to Example 1 can be applied to the fields of rock mass engineering, civil engineering, etc. The prepared rock-like material can truly restore the structure of natural rocks, providing technical support for research in related fields.
[0043] The structural properties of the rock-like material prepared according to the above method were compared with the rock material prepared by the traditional preparation method, and the results are shown in Table 1.
[0044] Table 1 Comparison results
[0045]
[0046] It can be found from Table 1 that the compressive strength of the rock-like material containing internal crack defects prepared in Example 1 can reach 70-100 MPa, which can reach the compressive strength standard of natural rock materials. It shows that the addition of nano-carbon silicon material modified rosin makes the strength of the rock-like material in Example 1 better than the rock-like material prepared by the traditional preparation method. At the same time, the addition of nano-carbon silicon material also enhances the toughness of the rock-like material, making the rock-like material prepared in Example 1 closer to the actual situation of restoring natural rocks. In addition, the number of cracks in the rock-like material of Example 1 is more evenly distributed than that of the traditional rock-like material. On the one hand, the prefabrication of the internal cracks of the rock-like material is completed, and on the other hand, the generation of internal cracks is easy to control.
[0047] Therefore, by adopting the above-mentioned method and application of preparing rock-like materials containing internal cracks and defects, the volatility of rosin modified by nano-carbon silicon material is utilized, and the rosin modified by nano-carbon silicon material is randomly buried in the rock-like material, thereby completing the prefabrication of internal cracks in the rock-like material, and making it easy to control the generation of internal cracks; at the same time, the rosin is modified by the nano-carbon silicon material, and the cracks formed after the rosin volatilizes and the nano-carbon silicon material remaining inside can reproduce the structural characteristics inside the rock, forming a microscopic structure similar to that of real rock, thereby increasing the authenticity of the rock-like material; at the same time, it also ensures that the rock-like material can simulate the structural characteristics of real rock, thereby further improving the scope of application of the rock-like material.
[0048] The principles and implementation methods of the present invention are described in this article using specific examples. The description of the above embodiments is only used to help understand the method and core idea of the present invention. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A method for preparing rock materials containing internal crack defects, characterized in that: The following steps are involved: Preparation of nano-carbon silicon material modified rosin; The process for preparing the nano-carbon silicon material modified rosin is as follows: first, rosin and nano-carbon silicon material are added to a stainless steel reactor, and then a volatile organic solvent is added to the stainless steel reactor, and the mixture is stirred evenly using a high-speed stirrer; then the stainless steel reactor is heated to a reflux state, the temperature is controlled between 60 and 80° C., and maintained for 1 to 2 hours; then, while maintaining the temperature, a crosslinking agent and an initiator are added dropwise, the mixture is stirred evenly, and the temperature of the stainless steel reactor is increased to between 80 and 100° C., and the mixture is reacted for 2 to 3 hours to promote the crosslinking reaction; after the reaction is completed, the mixed solution is cooled to room temperature, and then the remaining volatile organic solvent is removed by a decompression device to obtain the nano-carbon silicon material modified rosin; the volatile organic solvent is one of ethyl acetate, acetone, methanol, and ethanol; Select appropriate materials to prepare a mixed slurry of rock-like materials, and meet the particle grading requirements; the materials of the mixed slurry are composed of crushed stone, sand, cement, clay and water, and the mass ratio of the materials is: crushed stone: sand: clay: cement: water = 3:2:1:1:0.5, and the amount of the mixed slurry is determined according to the rock material required by the test; The nano-carbon silicon material modified rosin is mixed with the mixed slurry, and stirred evenly to obtain a mixture; Select and assemble a casting mold according to test requirements, slowly and evenly inject the mixture into the casting mold by laminar casting, vibrate and shape it, and maintain it under constant temperature and humidity conditions; After forming, the casting mold is removed, and the formed sample is placed in a heating furnace for high-temperature curing to obtain a rock-like material containing internal crack defects.
2. A method for preparing rock materials containing internal crack defects according to claim 1, characterized in that: The nano-carbon silicon material modified rosin is mixed with a mixed slurry, and stirred evenly to obtain a mixture. The specific method is: firstly, the mixed slurry is mixed and stirred evenly, and then the nano-carbon silicon material modified rosin is put into the mixed slurry, and stirred to a uniform state by a stirrer to obtain a mixture.
3. A method for preparing rock materials containing internal crack defects according to claim 1, characterized in that: The casting mold is selected and assembled according to the test requirements, the mixture is slowly and evenly injected into the casting mold by the laminar casting method, and vibrated into shape, and then cured under constant temperature and humidity conditions. The specific method is: the mixture in a uniform state is injected into the casting mold with a layered structure. After each layer is cast, the casting mold containing the mixture is placed on a vibration table for vibration to expel bubbles in the mixture.
4. A method for preparing rock materials containing internal crack defects according to claim 3, characterized in that: The constant temperature and humidity maintenance conditions are a temperature of 22-24° C. and a relative humidity of more than 90%.
5. The method for preparing rock materials containing internal crack defects according to claim 1, characterized in that: The formed sample is placed in a heating furnace for high-temperature curing to obtain a rock-like material containing internal crack defects, including: placing the formed sample in a heating furnace for curing for 24 hours, and the temperature of the heating furnace is maintained between 110 and 135° C., so that the nano-carbon silicon material modified rosin is heated and volatilized, and finally taking out the sample to obtain a rock-like material containing internal crack defects.
6. A rock material containing internal crack defects prepared according to the method for preparing a rock material containing internal crack defects according to any one of claims 1 to 5.
7. Use of the rock material containing internal crack defects according to claim 6 in geotechnical engineering.
Citation Information
Patent Citations
Brittle material for manufacturing rocks and preparation of specimen prefabricated crack thereof
CN101462854A
Manufacture method of rock sample with random fractures
CN103822808A